Essays in innovative risk management methods : based on deterministic, stochastic and quantum approaches - Desogus, Marco; Casu, Elisa (Anaphora Literary Press, 2018)
This analysis works towards overcoming the current business valuation logic as prevalently set by banks and other credit entities or, more generally, within risk capital markets. Current banking practice applies rigorous deterministic valuations that are based entirely on indices and ratios. Present accounting models are also poor representations of the correct money-credit-production-income mechanisms. This research proposes reforms for methods of business evaluation and determining the relative solidity or probability of insolvency. Each of the themes treated has its own identity, however they are integrated in relation to problems related to bank risk management and relevant creditworthiness assessments.